Structural analysis and co-crystallization of neurotransmitter analogues - Reece, Hayley A. (My University, 2009)
In recent years, the amino acid neurotransmitter γ-aminobutyric acid (GABA) has been widely studied for its significant inhibitory action in the central nervous system. Two polymorphs of GABA with different crystal systems have been reported in literature. A novel GABA solvate has been crystallized as thin needle-like single crystals. Through Xray single crystal diffraction analysis, this solvate was found to have a hexagonal crystal system and contain disordered solvent molecules in the asymmetric unit, which are found in channels created by the GABA molecules. 1H NMR allowed for the solvent to be identified as ethanol. This hexagonal GABA solvate is unique in that it is the first single amino acid to be crystallized in this form, where it has hexagonal channels which contain solvent molecules. Gabapentin (1-(aminomethyl)cycloheaxaneacetic acid) is a drug compound which is structurally related to GABA. It has been extensively studied due to interest in possible polymorphs and gabapentin analogues. Gabapentin exists as a zwitterion in the solid state. The crystal structures and bonding networks of two new monoclinic polymorphs (β- and γ-gabapentin) were studied using x-ray powder and single crystal diffraction. These polymorphs were compared with a previously reported gabapentin polymorph (α-gabapentin). All three polymorphs have extensive hydrogen bonding between the NH3 + and COO- groups of neighbouring molecules, with the β-gabapentin polymorph containing an additional weak intramoleular hydrogen bond. There have also been a number of reported studies on the co-crystallization of amino acids with various carboxylic acids. A significant feature in the co-crystallization of amino-carboxylic acid complexes includes the ionization states of the individual compounds used. The co-crystallization of neurotransmitter amino acids and their analogues with oxalic acid were carried out. Co-crystals of GABA-oxalic acid, gabapentin-oxalic acid and β-alanine-oxalic acid-water were formed at specific pH values. The crystal structures and hydrogen bonding networks of the co-crystals were analysed using X-ray diffraction techniques. Thermal analysis was carried out on all the structures as a means of comparing the melting points of different polymorphs and examining the possibility of phase transitions for each structure.